Effect of Workload on Job Stress of Inpatient Department Nurses in TNI-AU Dr. M. Salamun Hospital: The Role of Locus of Control as Moderator - Firda Ridhayanti; Sri Suwarsih; Handri Handri (Research Synergy Foundation, 2022)
Abstract Work stress is a familiar problem for workers, such as nurses. All hospital health workers are at risk of experiencing work stress in hospitals, but nurses have a higher risk of experiencing work stress. The high level of work stress in nurses is related to the main actors in health services that provide care for patients 24 hours a day. Nurses' many functions and duties include long working hours, night shifts, stressful conditions, and a high workload on nurses. This increased workload level is one of the main factors contributing to work stress in nurses. Coping with work stress requires a Locus of Control (LoC). A locus of control is an essential element possessed by every individual to control himself. Each individual has different control in different jobs. The researcher is doing this study to know the effect of workload on work stress with the LoC as the moderating variable. The data of this research takes using a total sampling of 125 nurses on duty in each inpatient room at the TNI-AU Dr. M. Salamun Hospital. This research is cross-sectional research with a quantitative analysis method using a research instrument in a questionnaire. The questionnaire consists of 3 parts related to workload, work stress, and LoC, with 64 questions. The study results showed that workload affected work stress (p-value < 0.001). The LoC variable is a quasi-moderating variable on the workload on work stress (p-value < 0.001).